Magnetic resonance brain: basic sequences and interpretation - Rivera, Diego Miguel; Pontificia Universidad Javeriana (Pontificia Universidad Javeriana, 2011)
Cerebral Magnetic Resonance Imaging has established itself as a valuable tool for the diagnosis of neurological diseases, due to its ability to provide excellent detail and tissue characterization.In this article explains the physical basis of MRI and the different sequences used in brain imaging protocol, in order to provide the reader with the basic tools for understanding images of the brain.